Geochemistry, Paragenesis, and Wall-Rock Alteration of the Qatruyeh Iron Deposits, Southwest of Iran: Implications for a Hydrothermal-Metasomatic Genetic Model. (22nd October 2014) - Asadi, Sina; Rajabzadeh, Mohammad Ali
Abstract : The Qatruyeh iron deposits, located on the eastern border of the NW-SE trending Sanandaj-Sirjan metamorphic zone, southwest of Iran, are hosted by a late Proterozoic to early Paleozoic sequence dominated by metamorphosed carbonate rocks. The magnetite ores occurred as layered to massive bodies, with lesser amounts of disseminated magnetite and hematite-bearing veins. Textural evidences, along with geochemical analyses of the high field strengths (HFSEs), large ion lithophiles (LILEs), and rare earth elements (REEs), indicate that the main mineralization stage occurred as low-grade layered magnetite ores due to high-temperature hydrothermal fluids accompanied by Na-Ca alteration. Most of the main ore-stage minerals precipitated from an aqueous-carbonic fluid (3.5–15 wt.% NaCl equiv.) at temperatures ranging between 300° and 410°C during fluid mixing process, CO2 effervescence, cooling, and increasing of pH. Low-temperature hydrothermal activity subsequently produced hematite ores associated with propylitic alteration. The metacarbonate host rocks are LILE-depleted and HFSE-enriched due to metasomatic alteration.